Unveiling Patriarchal Constructs: Exploring Saudi Women's Traditional Gender Roles and Gender Inequality Through Raja'a Alem's The Dove's Necklace - Rehab Moqbil (مجلة العلوم التربوية والدراسات الإنسانية سلسلة الآداب والعلوم التربوية والإنسانية والتطبيقية)
This study delves into a network of patriarchal societies within the Arab-Muslim world, particularly focusing on the construction of women's roles from a patriarchal perspective. It investigates how women's traditional gender roles are socially and culturally constructed and moulded at the hands of a male-dominated culture and societal norms through a deep exploration of Raja'a Alem's The Dove's Necklace novel and its connection to Saudi women. Both descriptive and analytical approaches to content analysis are employed to unravel the layers of women's traditional gender roles within a patriarchal framework through the feminism lens. The findings reveal a mould where women are directed toward fulfilling socially and culturally attributed roles, perpetuating a cycle of male dominance in shaping their societal identities. Furthermore, the study is a critique of societal norms and attitudes towards women, shedding light on the established inequalities and injustices they face. It underscores that women have long been in an inferior position that has been culturally rather than biologically constructed by a patriarchal system.